Fabrication of organic field-effect transistor-based biosensor - Ismadi, Irfan Danial; Mohamad Azmi, Muhammad Fakhrullah; Redzuan, Muhammad Fadzlisyam; Ibrahim, Izzah Afifah; Mohd Ghazali, Mohd Ifwat; Tamchek, Nizam; Mohamed, Nurul Azmawati; Abdullah, Shahino Mah (Universiti Teknologi MARA, Negeri Sembilan, 2025)
In this project, triisopropylsilylethynyl-pentacene (TIPS-pentacene) will be utilized as a semiconducting polymer matrix for the preparation of biosensors based on organic field-effect transistor (OFET) structure. A thin layer of TIPS-pentacene can be easily formed on a silicon substrate through solution processable technique. Through polymer blend method which allows synergistic combinations of stacking configurations of multiple polymers energy levels which will enhance overall charge transport. Novel pentacene derivatives will also be proposed using machine learning method and computational study for synthesizing new narrow energy band gap polymer matrix. Analytical techniques, such as ultraviolet-visible (UV-Vis) spectroscopy will be used in the characterization of the materials properties. The proposed biosensor based on integration of biological compound into OFET will facilitate the government.